The Effect of Different Nicotine Delivery Systems on Cardiovascular Health and Hemodynamic Load: A Literature Review - Dziemiańczuk, Jakub; Dryl-Jarmoc, Ewa; Ślinko, Izabela; Kuliś, Gabriela; Panas, Zuzanna; Krawczuk, Kacper; Zimowski, Mateusz; Kadysz, Piotr; Kolanek, Agata; Czajkowski, Mateusz (Quality in Sport, 2026)
Introduction: Active and passive smoking are leading global causes of cardiovascular (CVD) mortality, accounting for 2.25 million deaths annually (2021 data). Alternative nicotine delivery systems (e-cigarettes, heated tobacco products [HTP], snus, nicotine pouches) have surged in popularity, driven by aggressive marketing, 15,000 known flavor additives, and misconceptions of negligible harm, especially among youth. This study assesses how eliminating combustion in these products modifies CVD risk. Nicotine's independent role in atherosclerosis pathogenesis remains under investigation. It strongly stimulates the sympathetic nervous system, increasing plasma adrenaline up to 2.5-fold. This heightens hemodynamic load, potentially triggering acute CVD events, particularly in patients with existing cardiac conditions. Materials and methods: A PubMed literature review was conducted using keywords: "Nicotine pharmacokinetics", "Cardiovascular risk", "E-cigarettes", "Heated tobacco products", "Snus", "Nicotine pouches", "Endothelial dysfunction". Conclusions: Eliminating combustion (pyrolysis) significantly reduces released toxins compared to tobacco smoke. HTP aerosols contain >90% fewer harmful substances, and e-cigarettes release <2 µg of HPHC versus 3000 µg in tobacco. However, these products remain unsafe for the CV system. Nicotine's sympathomimetic effects increase blood pressure and heart rate, and exacerbate insulin resistance; animal studies indicate up to a 57% decrease in insulin-dependent glucose uptake. Furthermore, HTP and ENDS aerosols induce inflammation (increased IL-6, TNF-α, hsCRP), oxidative stress, and secondary vascular endothelial dysfunction. Popular flavor additives (cinnamaldehyde, eugenol, diacetyl) also demonstrate proven cytotoxic effects. Alternative nicotine products have high addictive potential and an undeniably negative CV impact, highlighting an urgent need for long-term health outcome studies.